《汉印尼语数词模糊义及修辞功用》 - SUSANTI SUSANTI (Journal International Lingua Mandarin (JILIN), 2021)
[摘要] 众所周知，语言是人类表达思想和交际的重要工具之一，在语言表达中一般要求精确性和具体性。但随着社会的发展，准确的数词也可转换为数词模糊义来表达，这些不准确数词的表达方式即模糊现象。本文主要考察汉语与印尼语数词模糊语义特征，以及考察两者的数词模糊义具有哪些修辞手法。通过对比考察发现，汉印尼语数词模糊义均可表示量多之意（程度高）和量少之意（程度低），虽然语义大多相同，但是汉语表数词模糊义的结构形式多于印尼语，因此需要注意。数词模糊义在修辞中可起到如临其境的良好效果。关键词：汉语与印尼语 数词模糊义 修辞功用 [Abstract] As we all know, language is one of the important tools for humans to express thoughts and communication, and accuracy and specificity are generally required in language expression. But with the development of society, accurate numerals can also be converted into numeral vague meanings to express. The expression of these inaccurate numerals is the phenomenon of vagueness. This article mainly examines the vague semantic features of Chinese and Indonesian numerals, and examines the rhetorical techniques of the vague meanings of numerals of the two. Through comparative investigation, it is found that the fuzzy meanings of Chinese and Indonesian numerals can both express the meaning of large quantity (high degree) and low quantity (low degree). Although the semantics are mostly the same, the structural forms of fuzzy meanings of Chinese numerals are more than those in Chinese. Indonesian, so you need to pay attention. The fuzzy meaning of numerals can play a good effect in the rhetoric.